Keamanan Data Internet of Things dalam Perspektif Pseudosains Mario Bunge: Internet of Things Data Security in Mario Bunge's Pseudoscience Perspective - Pradana, Aditya; Bandung, Yoanes; Mahayana, Dimitri; Rosmansyah, Yusep (Undiksha, 2024)
Data security is a major concern in the rapidly growing Internet of Things (IoT). This paper investigates the data security aspects of IoT with a pseudoscience perspective inspired by Mario Bunge. The purpose of this research is to understand and address data security challenges in IoT environments. First, researcher identify and evaluate potential vulnerabilities and threats to data, hacking risks, and data encryption needs. Then, researcher analyze commonly used security methods and strategies, including blockchain, fog computing, edge computing, and machine learning. Bunge's pseudoscience approach helps in comprehensively understanding and analyzing IoT data security. The results show a deeper understanding of the data security challenges in IoT, as well as detailed recommendations for risk mitigation. This research highlights the importance of a holistic approach that blends technical and philosophical aspects to address data security issues in IoT. The pseudoscience perspective helps in developing a solid conceptual framework and encourages critical thinking in formulating effective security strategies. In conclusion, this paper makes an important contribution in understanding and addressing the complexities of data security in IoT.